Mitral valve disease. Issue 10 (15th January 2014) - Ray, R.; Chambers, J.
Summary In industrially developed countries, moderate or severe mitral valve disease is relatively common and is usually caused by prolapse or is secondary to left ventricular disease. Mitral stenosis (MS), however, is uncommon and usually a sequela of rheumatic fever. This article discusses the natural history of mitral regurgitation and MS and their medical and surgical management.